Updates on controversies surrounding the staging and management of newly diagnosed localized prostate cancer using prostate-specific membrane antigen (PSMA) positron emission tomography - Patricia Tai; Patrick Martineau; Kelvin Wong; Evgeny Sadikov; Glenn Ollenberger; Kurian Joseph; Edward Yu; Derek Liu; Aoife Jones Thachuthara; Arbind Dubey; Rashmi Koul (Exploration of Medicine)
There are controversies surrounding indications for prostate-specific membrane antigen (PSMA) positron-emission tomography (PET) and the subsequent management of localized disease. Conventional imaging is not a necessary prerequisite to PSMA PET, which serves as an equally effective, if not more effective frontline imaging tool. However, research conducted in different countries has shown conflicting results regarding its cost-effectiveness. Following accurate staging using PSMA PET, subsequent management is discussed by our expert team in this review, which incorporates the latest updates: (1) Brief global overview: the sustainability and cost-effectiveness of routine PET, as well as the treatment sequences of neoadjuvant vs. adjuvant androgen deprivation therapy (ADT) with radiotherapy, require further research. (2) Gonadotropin-releasing hormone antagonists demonstrate better response rates, lower recurrence rates, and fewer complications compared to agonists. (3) The unfavorable intermediate-risk group may undergo prostatectomy or radiotherapy combined with 4–6 months of ADT. Radiotherapy alone may be considered for patients with co-morbidities, Gleason score 7 (3 + 4), and positive biopsy cores < 50%, provided an escalated radiation dose is applied. (4) Three Prostate Advances in Comparative Evidence (PACE) studies demonstrated that stereotactic radiotherapy, greatly relying on PSMA PET, is as effective as surgery or conventional radiotherapy. (5) Findings from clinical trials indicate that pelvic nodal radiotherapy coverage provides a survival benefit. (6) A brachytherapy boost provides better outcomes compared to external beam boost, eliminating the need for ADT in intermediate-risk cancers and reducing ADT duration to 6 months in high-risk cancers. Even short-term use (4–6 months) of gonadotropin releasing hormone agonists can lead to cardiac morbidity. In summary, localized prostate cancer, as identified through the relatively new PSMA PET, can be managed in various ways. This review highlights significant updates on controversial issues relevant to both cancer patients and researchers.